"I have travelled along on my own"—Experiences of seeking help for serious non‐COVID health problems during the COVID‐19 pandemic: A qualitative study. Issue 1 (26th July 2022) - Parretti, Helen M.; Belderson, Pippa; Eborall, Helen; Naughton, Felix; Loke, Yoon; Steel, Nick; Bachmann, Max; Hardeman, Wendy
Abstract: Objectives: During COVID‐19 the UK general population has been given strong messages to stay at home. Concurrently unprecedented changes occurred in healthcare access with moves to remote/triage systems. Data have shown that the number of people accessing healthcare services decreased and there are significant concerns that the pandemic has negatively affected help‐seeking for serious conditions, with potentially increased morbidity and mortality. An understanding of help‐seeking is urgently needed to inform public campaigns. We aimed to develop an in‐depth, theory‐based understanding of how, when and why people sought help for potentially serious symptoms (e.g., related to major cardiovascular events or cancer diagnoses) during the pandemic, and what influenced their decisions. Design: Qualitative semi‐structured interviews. Methods: We interviewed 25 adults recruited through a targeted social media campaign. Interviews were conducted via telephone or online platform. Our topic guide was informed by the Model of Pathways to Treatment and the Capability‐Opportunity‐Motivation‐Behaviour model. Results: The analysis identified four main themes: Delay in recognition, Holding on to concerns, Weighing it up and Long‐term impacts . Multiple societal and environmental factors influenced participants' help‐seeking and motivation, capability and opportunity to seek help, with long‐term impacts on well‐being and future help‐seeking. Conclusions: There is a need for clear guidance about pathways to raise concerns about symptoms and gain advice while usual healthcare contacts are paused or stopped. Recommendations for future interventions to support help‐seeking during pandemics include clearer messaging, co‐produced with end‐users, on when, where and how to seek help.